Eales’ Disease in Inuit: A Short Report and Clinical Update - Forshaw TRJ; Moldow B (International Medical Case Reports Journal)
Thomas Richard Johansen Forshaw,1,2 Birgitte Moldow1,3 1Department of Ophthalmology, Rigshospitalet-Glostrup, Glostrup, Denmark; 2Department of Ophthalmology, Sygehus Sønderjylland, Sønderborg, Denmark; 3Faculty of Health and Medical Sciences, University of Copenhagen, Copenhagen, DenmarkCorrespondence: Thomas Richard Johansen Forshaw, Department of Ophthalmology, Sygehus Sønderjylland, Sydvang 1, 6400 Sønderborg, Denmark, Tel +45 79975800, Email forshawthomas@yahoo.co.ukPurpose: We report a case of Eales disease in Inuit and reflect on advances in telemedicine and treatment of retinal disease since the first report of Eales’ disease in Greenlandic Inuit was published.Patients and Methods: A 41-year-old Inuit female complaining of blurred vision was referred to our eye department. There had been no sign of diabetic retinopathy during diabetic eye screening and the patient had been treated for tuberculosis in 2010. Telemedical assessment was suspicious for vitritis or vitreous hemorrhage in the right eye, and the patient was flown from Greenland to Denmark, where examination revealed mild vitritis in the right eye, vitreous hemorrhage in the left eye and retinal neovascularization in both eyes. Fundus fluorescein angiography showed vessel leakage and areas of retinal non-perfusion. There was left epiretinal membrane with retinal thickening on macular optical coherence tomography.Results: Based on the patient’s clinical findings and history of tuberculosis infection, a diagnosis of Eales’ disease was made. The left eye was treated with pars plana vitrectomy with epiretinal membrane peeling, endodiathermy and endolaser. The right eye was treated in outpatients with sectoral laser photocoagulation. At seven weeks’ follow-up, the visual acuity had improved from 6/12 to 6/6 (right eye) and from 6/36 to 6/7.5 (left eye).Conclusion: The prevalence of tuberculosis in Greenland is very high and it is recommended that clinicians remain alert to the possibility of Eales’ disease, as beneficial visual outcomes are associated with prompt diagnosis and treatment. Telemedicine allows more frequent follow-up of Greenlander patients.Keywords: Eales’ disease, Greenlandic Inuit, telemedicine, tuberculosis